The KEBIJAKAN PENANGANAN ANAK : BAGAIMANA PERAN PEMERINTAH DALAM MENANGANI PERMASALAHANNYA - Agustin Widjiastuti (Jurnal Hukum Lex Generalis, 2024)
Reading news from the media, there will be many questions about children's rights that they must get, such as the right to education, proper care, neglect, freedom of speech, freedom from all forms of abuse. Children's rights are their basic rights that must be fulfilled. We can see and feel various cases, this treatment can occur within the family / household or outside the family / household. From various events that befell children that have not been revealed for any reason, the Government must take responsibility. This has been included in the 1945 Constitution of the Republic of Indonesia and Law no. 39 of 1999. Delays in handling children's problems with all their connections will have a negative impact on both the child himself and the Government. Therefore, the Government must immediately take legal steps with serious policies in overcoming the problems of Indonesian children as the next generation of the nation. The use of research methods with a normative juridical type through the Statue Approach, Conceptual Approach, Philosophical Approach. Based on the results of discussions by the Government and related parties, many legal regulations have been produced that provide protection for children, but in reality there are still many children who do not get their rights, even in practice we often see children receiving treatment that they should not receive. What legal steps can a child take to get their rights, namely preventive and curative legal protection and rehabilitation. Therefore, the Government must revise the law and seriously implement the concept of protection for children's problems and supervise related parties in implementing the vision and mission that have been agreed upon together so that discrimination does not occur.